Some Nonlinear Approximations for Matrix-Valued Functions (Journal of Computational Mathematics, 2021)
Some nonlinear approximants, i.e., exponential-sum interpolation with equal distance or at origin, (0,1)-type, (0,2)-type and (1,2)-type fraction-sum approximations, for matrix-valued functions are introduced. All these approximation problems lead to a same form system of nonlinear equations. Solving methods for the nonlinear system are discussed. Conclusions on uniqueness and convergence of the approximants for certain class of functions are given.
Keywords: Matrix-valued function; Nonlinear approximation; Interpolation.